Impact of preanalytical sample preparation on the recovery rate of cryopreserved allogeneic hematopoietic stem cells - Blüm, Philipp; Glas, Christina; Bieback, Karen; Kayser, Sabine; Klüter, Harald; Wuchter, Patrick (European journal of haematology, 2026)
Introduction Cryopreservation of peripheral-blood-derived hematopoietic stem and progenitor cells (PBSCs) has been used for decades, primarily for autologous transplantation. Now, in the era of new cellular therapies, the cryopreservation of allogeneic PBSCs may also become relevant. While the defining quality-control parameters are assessed before cryopreservation, in thawed cryopreserved samples the viability of total nucleated cells is often the only parameter analyzed. We therefore evaluated the recovery rates of total and viable CD45+ and CD34+ cells after cryopreservation. Methods Thirty-nine samples of allogeneic PBSC products were analyzed before and after cryopreservation. Post-thaw viability was assessed using trypan blue exclusion. To investigate the influence of different preanalytical preparation methods, PBSCs were resuspended in phosphate-buffered saline (PBS) or human serum albumin (HSA), and the cells suspended in HSA were tested without incubation or following incubation at 37°C for 1 h or 2 h. The number and viability of CD45+ and CD34+ cells were evaluated by flow cytometry and compared with pre-thaw values. Results After cryopreservation, we observed significant decreases in both total and viable CD45+ cell numbers. In contrast, the difference in total CD34+ cell numbers was rather small, whereas the median recovery rate of viable CD34+ cells after resuspension in PBS was 70.1%. Relevant differences between the preanalytical treatment groups could not be observed. The viability values as determined by trypan blue viability staining and flow cytometry were not correlated. Conclusion Determination of the CD34+ cell recovery rate after thawing is feasible and may be used as an additional parameter for quality control for cryopreserved allogeneic PBSCs. However, the results of currently used viability assays vary considerably, making comparisons between different cell processing units and cryopreservation protocols difficult. Therefore, available protocols should be carefully evaluated based on “good-manufacturing-practice” (GMP) regulations before implementation.